Mental Health Apps in China: Analysis and Quality Assessment - Shang, Jie; Wei, Shaoming; Jin, Jianbo; Zhang, Puhong (JMIR Publications, 2019)
BackgroundMental disorders have been a great burden on health care systems, affecting the quality of life of millions of people worldwide. Developing countries, including China, suffer from the double burden of both the increasing mental health issues in population and the deficiency in mental health care resources. The use of mobile health technologies, especially for mobile phone apps, can be a possible solution. ObjectiveThis review aimed to describe the features and assess the quality of mental health apps in major mobile phone app markets in China and further discuss the priorities for mental health app development. MethodsKeywords including psychology, psychological health, psychological hygiene, psychological health service(s), mental, mental health, mental hygiene, mental health service(s), depression, and anxiety were searched in Chinese in 3 Android app markets (Baidu Mobile Assistant, Tencent MyApp, and 360 Mobile Assistant) and iOS App Store independently. Mental health apps were then selected according to established criteria for in-depth analysis and quality assessment by the Mobile App Rating Scale. ResultsIn total, 63 of 997 mental health apps were analyzed in depth, of which 78% (49/63) were developed by commercial entities for general population, 17% (11/63) were for patients or clients of specialized psychiatric hospitals or counseling agencies, 3% (2/63) were by government or local Centers for Disease Control and Prevention for general information, and 2% (1/63) for students of a university. Major built-in features of the apps included counseling services, mental health education, and self-assessment of mental health status by validated self-rating scales. The overall quality score of the MH apps was acceptable. ConclusionsMental health apps are emerging in the area of mobile health in China. Popular mental health apps usually provide a synthetic platform organizing resources of information, knowledge, counseling services, self-tests, and management for the general population with mental health-related inquiries. The quality of the apps was rated as acceptable on average, suggesting some space for improvement. Official guidelines and regulations are urgently required for the field in the future.